Method for preparing selenium-based diatomic catalyst through high-temperature atomization method and application of selenium-based diatomic catalyst
The preparation of Se-Fe diatomic catalysts through high-temperature "atomization method" solved the problem of insufficient catalytic performance of zinc-air batteries under low temperature conditions, and achieved efficient catalyst preparation and significant improvement in battery performance.
Patent Information
- Application Number
- CN202510093231.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-21
- Publication Date
- 2025-04-08
AI Technical Summary
The prior art is difficult to effectively improve the oxygen reduction catalytic performance of rechargeable and discharged zinc-air batteries under low temperature conditions, resulting in serious deterioration of battery performance.
The selenium powder and Fe/ZIF-8 were mixed and carbonized by high-temperature "atomization method" to prepare a Se-Fe diatomic catalyst. By adjusting the preparation method of Fe/ZIF-8, the atomic utilization and stability of the metal SeFe components were achieved by adjusting the atomicity of Fe/ZIF-8.
The catalytic activity and electrochemical performance of the catalyst are significantly improved, the activity and endurance of low-temperature rechargeable and dischargeable zinc-air batteries are improved, and the catalyst shows good stability under low temperature conditions.
Smart Images

Figure CN119786629A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to a method for preparing a selenium (Se)-based diatomic catalyst by a high-temperature "atomization method", and in particular to a method for preparing a selenium (Se)-based diatomic catalyst for a low-temperature chargeable and dischargeable zinc-air battery, belonging to the technical field of catalyst preparation. Background Art
[0002] The development of sustainable clean energy requires major breakthroughs in new energy technologies, such as water electrolysis devices, fuel cells, and metal-air batteries. Rechargeable zinc-air batteries (ZABs) have attracted extensive attention due to their high energy density (1086Wh / kg), abundant natural zinc reserves, low cost, and high safety. However, when the temperature is below 0°C, the performance of ZABs deteriorates severely due to the sluggish kinetics of the electrocatalytic reaction and the high O=O bond breaking energy barrier (up to 498kJ / mol). These problems are mainly due to the lack of efficient and stable oxygen reduction (ORR) electrocatalysts. Although a lot of work has been done on designing high-performance ORR catalysts, there is still much room for improvement.
[0003] Atomically dispersed metal-based electrocatalysts have attracted the attention of researchers due to their nearly 100% atomic utilization and excellent catalytic performance. Among them, carbon-supported single-atom catalysts (especially Fe-N4 / C) with metal-nitrogen atomic sites are ideal candidate catalysts for electrocatalytic reactions. However, the highly electronegative N-coordinated Fe sites lead to low electron density at the Fe center, and the adsorption energy of oxygen intermediates (such as OOH*, O*, *O2, and OH*) becomes weaker. In addition, for single-atom catalysts, oxygen intermediates prefer to adsorb onto active sites through side or end positions. This single-site adsorption mode inevitably leads to a higher energy barrier for OO bond cleavage, making performance enhancement challenging.
[0004] The ORR performance of the catalyst can be effectively improved by constructing a diatomic catalyst. The diatomic catalyst usually has a strong interaction between two adjacent sites: i) the diatomic site can change the adsorption energy of the intermediate through strong oxygen adsorption ability; ii) the diatomic site can reduce the reaction energy barrier through electronic effect and synergistic effect; iii) the diatomic site can change the reaction route and improve the reaction kinetics based on the diatomic site to O-containing intermediates. Therefore, the diatomic site can well regulate the adsorption state of the ORR intermediate, which is conducive to the cleavage of the OO bond, and thus is expected to improve the catalytic activity. Selenium (Se) is a chalcogen element with similar chemical properties to N and greater polarization. Incorporating Se into Fe-based NC materials to coordinate metal sites can form an atomic pair site configuration, while enhancing the electron density of the Fe site, significantly improving the catalytic performance of the material.
[0005] The method of using a metal organic framework with a three-dimensional porous structure as a carbon precursor, dispersing the doped metal precursor salt on the surface of the metal organic framework, and then preparing a selenium-based diatomic catalyst by selenization has been proven to effectively improve the catalytic activity of the catalyst. For example, patent CN 117832521 A discloses a method for preparing a Co / Se diatomic site ORR catalyst supported by ZIF-derived porous carbon, wherein an organic ligand, a zinc precursor, and a cobalt precursor are respectively dissolved in methanol, mixed and reacted, and then dried to obtain a precursor, and the precursor powder is calcined and then mixed with selenium dioxide powder for carbonization to prepare a ZIF-derived porous carbon-supported Co / Se diatomic site ORR catalyst. Although this method obtains a Co / Se diatomic catalyst with enhanced ORR catalytic performance, the catalytic performance of the prepared catalyst is still poor. The main reason is that this method first carbonizes the CoNC material and then introduces the Se element. It is difficult for Se to enter the carbon skeleton, and the Co-Se interaction is weak, resulting in low performance. Patent CN115332547A discloses a method for preparing a Cu, Se diatomic catalyst, which comprises preparing a metal organic framework by mixing an organic ligand and a zinc precursor, then mixing the copper precursor with the metal organic framework to obtain Cu-ZIF, and finally mixing it with diphenyl diselenide to carbonize to obtain a Cu, Se diatomic catalyst. Although the catalyst prepared by this method can improve its catalytic performance to a certain extent, the catalytic performance of the catalyst is still difficult to meet the requirements of a low-temperature rechargeable zinc-air battery.
[0006] Therefore, developing a feasible method to prepare Se-Fe catalysts with high performance has very important application value. Summary of the invention
[0007] In order to solve the above technical problems, the purpose of the present invention is to provide a method for preparing Se-based diatomic catalysts by high-temperature "atomization method", by selecting selenium powder and preparing Fe / ZIF-8 mixed carbonization, and adjusting the preparation method of Fe / ZIF-8 material to prepare Se-based diatomic catalysts. The preparation method of the present invention can effectively synthesize Se-based diatomic catalysts, and the metal SeFe component can achieve nearly 100% atomic utilization, and can also be firmly stabilized on the carbon carrier.
[0008] In view of the above purpose, the present invention first provides a method for preparing a Se-based diatomic catalyst by a high-temperature "atomization method", comprising the following steps:
[0009] (1) dissolving 2-methylimidazole in a mixture of methanol and dimethylformamide (DMF) and stirring to obtain a solution A; dissolving a zinc precursor salt and a Fe precursor salt in a mixture of methanol, DMF and ethylene glycol and stirring to obtain a solution B; mixing the solution A and the solution B, stirring, washing the product obtained after centrifugation with methanol three times, and drying to obtain Fe / ZIF-8;
[0010] (2) In an Ar atmosphere, the Fe / ZIF-8 obtained in step (1) and Se powder are mixed uniformly by grinding, and the mixed powder is carbonized at a high temperature of 700 to 1200° C., and then naturally cooled to room temperature to obtain a Fe-Se / NC diatomic catalyst.
[0011] In one embodiment of the present invention, in step (1), the concentration of 2-methylimidazole in solution A is 0.6-1.0 mol / L.
[0012] In one embodiment of the present invention, in step (1), the volume ratio of methanol to DMF in solution A is 1:5 to 1:1.
[0013] In one embodiment of the present invention, in step (1), the concentration of the zinc precursor salt in the B solution is 0.01-0.1 mol / L, and the concentration of the Fe precursor salt is 0.001-0.01 mol / L, the zinc precursor salt includes at least one of zinc nitrate, zinc chloride, zinc sulfate, zinc acetate, and zinc acetylacetonate, and the Fe precursor salt includes at least one of triacetylacetonate iron, ferric nitrate, ferric chloride, ferric sulfate, ferric acetate, and ferrous chloride.
[0014] In one embodiment of the present invention, in step (1), the volume ratio of methanol, DMF and ethylene glycol in solution B is 1:1:1 to 1:5:1.
[0015] In one embodiment of the present invention, in step (1), the volume ratio of solution A and solution B when mixed is 1:5 to 1:1.
[0016] In one embodiment of the present invention, in step (1), the stirring speed is 400-800 r / min, and the stirring time is 10-60 min.
[0017] In one embodiment of the present invention, in step (1), the rotation speed during centrifugation is 6000-10000 rpm, and the centrifugation time is 5-20 min.
[0018] In one embodiment of the present invention, in step (1), the drying refers to vacuum drying at 50-100° C., the vacuum degree during vacuum drying is 70-100 kPa, and the drying time is 4-12 h.
[0019] In step (1) of the present invention, all operations except drying are carried out at room temperature, which refers to 15 to 35°C.
[0020] In one embodiment of the present invention, in step (2), the mass ratio of Fe / ZIF-8 to Se powder is 20:1 to 5:1.
[0021] In one embodiment of the present invention, in step (2), carbonization is carried out in a tubular furnace. During carbonization, the temperature is first raised to 700-1200° C. at a heating rate of 5° C. / min, and then maintained for 2-5 hours.
[0022] The invention also discloses a Fe-Se / NC diatomic catalyst prepared according to the method.
[0023] The invention discloses application of the catalyst in oxygen electric reduction and low-temperature chargeable and dischargeable zinc-air battery.
[0024] Beneficial effects:
[0025] 1. The present invention uses selenium powder as a selenium source, mixes it with a metal organic framework coated with iron ions for carbonization, and the bonding energy barrier between the selenium powder and the Fe site is low, which is conducive to the formation of a Se-Fe diatomic catalyst. The catalyst prepared by the method of the present invention can catalyze the electroreduction of oxygen to water, while improving the performance of a low-temperature rechargeable zinc-air battery.
[0026] 2. The preparation method of the Se-Fe diatomic catalyst of the present invention utilizes the selenium powder atomization strategy and the carbonization process of the metal organic framework to obtain a porous carbon material, which can significantly increase the contact area between the catalyst active center and the reactant, and accelerate charge transfer and material transport, further improving the electrochemical performance.
[0027] 3. The Se-Fe diatomic catalyst provided by the present invention can effectively improve the activity and endurance of low-temperature rechargeable zinc-air batteries; in addition, the electronic structure of the metal active center can be optimized through electronic interaction between the Se-Fe diatoms, and coordination with nitrogen and carbon heteroatoms can further improve the surrounding charge distribution of Se and Fe, thereby improving the catalytic performance and cycle stability.
[0028] 4. The catalyst prepared by the method of the present invention is loaded on the working electrode to prepare a zinc-air battery, and the power density of the battery is as high as 135mW / cm 2 ), even at -40°C, at 1mA / cm 2 The current density can continue to work for 741h (4041 cycles) without obvious performance degradation. 2The battery can work continuously for 133 hours (725 cycles) at a current density of 1.5 MW without obvious performance degradation. Moreover, the working battery can work normally under conditions such as bending, puncture or cutting. BRIEF DESCRIPTION OF THE DRAWINGS
[0029] Figure 1 This is an electron microscope image of the catalyst in Example 1.
[0030] Figure 2 The X-ray diffraction patterns of the catalysts of Example 1, Comparative Example 1 and Comparative Examples 3-4 are shown.
[0031] Figure 3 The Raman spectra of Example 1 and Comparative Examples 3-4 are shown.
[0032] Figure 4 Graph showing oxygen electroreduction performance of the catalysts of Example 1 and Comparative Examples 1 to 4.
[0033] Figure 5 This is a performance diagram of the oxygen electroreduction stability of the catalyst in Example 1.
[0034] Figure 6 This is a comparison chart of the energy density of flexible zinc-air batteries prepared using the catalysts of Example 1 and Comparative Example 2 at room temperature (25°C) and low temperature (-40°C).
[0035] Figure 7 The current density of the flexible zinc-air battery prepared by using the catalysts of Example 1 and Comparative Example 2 under low temperature conditions is 1 mA cm -1 and 5mAcm -1 Cyclic stability diagram under different conditions.
[0036] Figure 8 This is a physical picture of the zinc-air battery of Example 1. DETAILED DESCRIPTION
[0037] In order to explain the production process and principle of the present invention in more detail, embodiments are given, which are only for explanation and description and are not intended to limit the scope of the present invention.
[0038] All electrochemical measurements involved in the examples and comparative examples were performed on a CHI 630E electrochemical workstation using a three-electrode system. The working electrode was a rotating disk electrode (RDE). A carbon rod was used as the counter electrode, and a saturated calomel electrode (SCE) was used as the reference electrode. All potentials were converted to RHE standards according to E(RHE)=E(SCE)+0.059pH+0.2415.
[0039] Test method:
[0040] 6 mg of the sample was dispersed in 960 μL of ethanol and 40 μL of 5% Nafion solution, and ultrasonicated for 0.5 h to obtain a uniform catalyst ink. During the electrochemical test, 10 μL of the obtained catalyst ink was drop-coated on the working electrode and air-dried naturally. The treatment method of other control samples and commercial Pt / C was the same as that of the catalyst. The electrochemical tests were all carried out in 0.1 M KOH (pH = 13) solution, saturated with O2 or N2 at room temperature. Unless otherwise stated, all scan rates were 5 mV / s.
[0041] Flexible zinc-air battery assembly
[0042] 1.5 g of acrylamide (AM), 3 mg of NN methylenebisacrylamide (MBA) and 7 mg of potassium persulfate (KPS) were added to a mixed solvent of 10 mL of deionized water and dimethyl sulfoxide (DMSO) (deionized water: DMSO = 1:1) to prepare an organic gel polymer electrolyte. Then 0.1 M zinc perchlorate was added and stirred for 0.5 h, and polymerized at 60 ° C for 12 hours to obtain a polyacrylamide (PAM) organic hydrogel. After cooling, the PAM organic hydrogel was soaked in a 6 M KOH + 0.2 M Zn (OAc) 2 solution for 24 hours and then taken out. It was then wrapped around the zinc anode, and an air electrode loaded with a catalyst was placed on the outermost layer to form a flexible cable structure battery.
[0043] Example 1
[0044] A method for preparing a Se-Fe diatomic catalyst by a high temperature "atomization method" comprises the following steps:
[0045] 2-Methylimidazole (1314 mg) was dissolved in 8 mL of methanol and 12 mL of N-N-DIMETHYLFORMIDE solution, which was recorded as solution A. Zn(NO3)2·6H2O (1190 mg) and Fe(acac)3 (70.6 mg) were dissolved in 12 mL of methanol, 36 mL of N-N-DIMETHYLFORMIDE and 12 mL of ethylene glycol solution, and dissolved under ultrasound for 15 min to form solution B. Then, solution A was added to solution B and stirred at room temperature for 24 h. The obtained product was separated by centrifugation, then washed three times with methanol, and finally dried at 70 °C in vacuum overnight to obtain Fe / ZIF-8. The above product was mixed with 10 mg of Se powder by grinding. Then, the ground sample was transferred to a quartz boat and placed in a tube furnace for carbonization. During carbonization, the sample was heated to 950 °C at a heating rate of 5 °C / min, calcined under flowing argon for 3 h, and then cooled naturally to room temperature. The obtained material was marked as Fe-Se / NC-1 and used directly without further treatment. The contents of Se and Fe in the sample were determined by ICP-MS, where the loading amount of Se was 1.93 wt % and the loading amount of Fe was 2.06 wt %.
[0046] Example 2
[0047] 2-Methylimidazole (1314 mg) was dissolved in 8 mL methanol and 12 mL N-N-dimethylformamide solution, which was recorded as solution A. Zn(NO3)2·6H2O (1190 mg) and Fe(acac)3 (70.6 mg) were dissolved in 12 mL methanol, 36 mL N-N-dimethylformamide and 12 mL ethylene glycol solution, and dissolved under ultrasound for 15 min to form solution B. Then A was added to B and stirred at room temperature for 24 h. The obtained product was centrifuged, then washed three times with methanol, and finally dried overnight at 70 ° C in vacuum to obtain Fe / ZIF-8. The above Fe / ZIF-8 powder was ground and calcined at 950 ° C in a nitrogen atmosphere for 3 hours to obtain Fe / NC powder; then the above Fe / NC powder was mixed with 10 mg Se powder by grinding. Then, the ground sample was transferred to a quartz boat and placed in a tube furnace for carbonization. During carbonization, the sample was heated to 600 °C at a heating rate of 5 °C / min, calcined for 3 h under a flowing argon atmosphere, and then naturally cooled to room temperature. The obtained material was labeled Fe-Se / NC-2 and used directly without further treatment.
[0048] Example 3
[0049] 2-Methylimidazole (1314 mg) was dissolved in 20 mL of methanol solution, which was recorded as solution A. Zn(NO3)2·6H2O (1190 mg) and Fe(acac)3 (70.6 mg) were dissolved in 60 mL of methanol solution and dissolved under ultrasound for 15 min to form solution B. Then A was added to B and stirred at room temperature for 24 h. The obtained product was separated by centrifugation, then washed three times with methanol, and finally dried overnight in vacuum at 70 °C to obtain Fe / ZIF-8. The above product was mixed with 10 mg of Se powder by grinding. Then, the ground sample was transferred to a quartz boat and placed in a tube furnace for carbonization. During carbonization, the sample was heated to 950 °C at a heating rate of 5 °C / min, calcined under flowing argon for 3 h, and then naturally cooled to room temperature. The obtained material was marked as Fe-Se / NC-3 and used directly without further treatment.
[0050] Comparative Example 1
[0051] The difference between Comparative Example 1 and Example 1 is that Fe(acac)3 is not added during the preparation of the catalyst, and Se powder is not added during the carbonization process, and is named NC.
[0052] Comparative Example 2
[0053] The difference between Comparative Example 2 and Example 1 is that a commercial platinum-carbon (Pt / C) electrocatalyst is used instead of the Fe-Se / NC-1 catalyst in Example 1 for testing, and is named Pt / C.
[0054] Comparative Example 3
[0055] The difference between Comparative Example 3 and Example 1 is that Fe(acac)3 is not added during the preparation of the catalyst, and is named Se / NC.
[0056] Comparative Example 4
[0057] The difference between Comparative Example 4 and Example 1 is that Se powder is not mixed during the carbonization process, and it is named Fe / NC.
[0058] Comparative Example 5
[0059] The difference between Comparative Example 5 and Example 1 is that the amount of Se powder added is changed to 5 mg.
[0060] Comparative Example 6
[0061] The difference between Comparative Example 6 and Example 1 is that the amount of Se powder added is changed to 15 mg.
[0062] Comparative Example 7
[0063] The difference between Comparative Example 7 and Example 1 is that Se powder is replaced by selenium dioxide.
[0064] Comparative Example 8
[0065] The difference between Comparative Example 8 and Example 1 is that the Se powder is replaced by diphenyl diselenide.
[0066] The oxygen reduction test results of Examples 1 to 3 and Comparative Examples 1 and 3 to 8 are shown in Table 1. As can be seen from Table 1, Example 1 has the best oxygen reduction performance (including activity and stability). The reason for the poor performance of Example 2 is that the Se powder is mixed with the carbonized Fe / ZIF-8 and calcined, resulting in the inability of Se atoms to enter the Fe-based carbon skeleton to form Se-Fe bonds under high temperature conditions, so the regulation effect is weakened and the performance is poor. The reason for the poor performance of Example 3 is that the Fe / ZIF-8 particle size is larger (about 500nm) with a single reaction solution of methanol, which is much larger than the 200nm of Example 1. The larger particle size is not conducive to the exposure of active sites, resulting in poor performance. Comparative Example 1 is a NC carrier that does not contain Fe and Se, so it has the worst performance. Comparative Examples 3 and Comparative Examples 4 are single-atom catalysts with Se and Fe as single metals as active sites, respectively, so the performance is lower than that of Example 1. Examples 5 and 6 illustrate that excessive use of Se will cause performance degradation. 10mg of Se powder is the optimal amount. The lower performance of Example 7 indicates that selenium dioxide is not a good selenium source because the bonding barrier between selenium dioxide molecules and Fe sites is high, which is not conducive to the formation of Se-Fe diatomic catalysts. The poor performance of Example 8 is due to the fact that the benzene intermediate in diphenyl diselenide will couple into the carbon skeleton, forming carbon deposits covering the active sites.
[0067] Table 1 Oxygen reduction test data of Examples 1 to 3 and Comparative Examples 1 and 4 to 9
[0068]
[0069]
[0070] According to the method of preparing Se-Fe diatomic catalyst by high temperature "atomization method" in Example 1, Se-Fe diatomic catalyst was successfully prepared. Figure 1 From the dark field transmission electron microscope image (a), it can be seen that the prepared Example 1 has a porous carbon skeleton structure, which is conducive to material transport and exposure of more active sites. Figure 1 (b) is a spherical aberration corrected scanning electron microscope image, from which it can be seen that a large number of active sites exist on the carbon support in an atomically dispersed state without atomic aggregation. It also shows that this preparation method is effective for the preparation of diatomic catalysts. Figure 2 2 are the X-ray diffraction spectra of the samples of Example 1, Comparative Example 1 and Comparative Examples 3-4. It can be seen from the figure that the samples of Example 1, Comparative Example 1 and Comparative Examples 3-4 all behave as typical amorphous carbon materials, and no single substance and oxidation signal peaks corresponding to Se and Fe are detected. Figure 3 The Raman spectra of Example 1, Comparative Example 3 and Comparative Example 4 show that when Se and Fe atoms coexist, I D / I GThe value of is significantly increased, indicating that there are a large number of defect structures in the surface embodiment 1, which is beneficial to improving the electrochemical performance. Figure 4 The oxygen electroreduction performance curves of the five catalysts of Example 1 and Comparative Examples 1 to 4 are shown in the figure. It can be seen from the figure that Example 1 has the best electrocatalytic performance, and its starting potential and half-wave potential are 1.05V and 0.925V respectively, which are much higher than those of other catalysts. Figure 5 The LSV curve of Example 1 before and after 5000 cycles is shown, and the half-wave potential loss is only 5 mV, indicating that Example 1 has very good stability.
[0071] A flexible zinc-air battery with a cable structure was prepared using Example 1 and Comparative Example 2 as air cathodes, -40°C resistant modified organic hydrogel PAM as electrolyte, and a zinc plate as an anode. Figure 6 The power density curves of the flexible zinc-air battery ZABs-Fe-Se / NC-1 prepared in Example 1 and the comparative battery ZABs-Pt / C prepared using the catalyst of Comparative Example 2 at 25°C and -40°C are shown. It can be seen from the figure that both Example 1 exhibits higher performance parameters (power density of 135 mW / cm 2 ). Figure 7 The zinc-air battery assembled in Example 1 is shown to have a current of 1 mA / cm at -40°C. 2 The current density can continue to work for 741h (4041 cycles) without obvious performance degradation. 2 The current density can continue to work for 133h (725 cycles) without obvious performance degradation. Figure 8 The working battery assembled according to Example 1 can work normally under conditions such as bending, puncture or cutting.
[0072] Compared with commercial catalysts, the present invention shows that the Se-Fe diatomic catalyst has better catalytic performance and lower use cost under the condition of low noble metal usage, and has high industrial application prospects.
[0073] The embodiments provided above are not intended to limit the scope of the present invention, and the steps described are not intended to limit the execution order thereof. Those skilled in the art may make obvious improvements to the present invention in combination with existing common knowledge, which also fall within the scope of protection defined by the claims of the present invention.
Claims
1. A method for preparing Se-based diatomic catalysts by high temperature "atomization method", characterized in that: The following steps are involved: (1) dissolving 2-methylimidazole in a mixture of methanol and DMF and stirring to obtain a solution A; dissolving a zinc precursor salt and an Fe precursor salt in a mixture of methanol, DMF and ethylene glycol and stirring to obtain a solution B; mixing the solution A and the solution B, stirring, washing the product obtained after centrifugation with methanol three times, and drying to obtain Fe / ZIF-8; (2) In an Ar atmosphere, the Fe / ZIF-8 obtained in step (1) and Se powder are mixed uniformly by grinding, and the mixed powder is carbonized at a high temperature of 700 to 1200° C., and then naturally cooled to room temperature to obtain a Fe-Se / NC diatomic catalyst.
2. The method according to claim 1, characterized in that In step (1), the concentration of 2-methylimidazole in solution A is 0.6 to 1.0 mol / L, and the volume ratio of methanol to DMF in solution A is 1:5 to 1:
1.
3. The method according to claim 1, characterized in that In step (1), the concentration of the zinc precursor salt in solution B is 0.01 to 0.1 mol / L, and the concentration of the Fe precursor salt is 0.001 to 0.01 mol / L. The zinc precursor salt includes at least one of zinc nitrate, zinc chloride, zinc sulfate, zinc acetate, and zinc acetylacetonate. The Fe precursor salt includes at least one of triacetylacetonate iron, ferric nitrate, ferric chloride, ferric sulfate, ferric acetate, and ferrous chloride. The volume ratio of methanol, DMF, and ethylene glycol in solution B is 1:1:1 to 1:5:
1.
4. The method according to claim 1, characterized in that: In step (1), the volume ratio of solution A and solution B when mixed is 1:5 to 1:
1.
5. The method according to claim 1, characterized in that The stirring speed is 400-800 r / min, the stirring time is 10-60 min, the centrifugal speed is 6000-10000 rpm, and the centrifugal time is 5-20 min.
6. The method according to claim 1, characterized in that In step (1), the drying refers to vacuum drying at 50-100° C., the vacuum degree during vacuum drying is 70-100 kPa, and the drying time is 4-12 hours.
7. The method according to claim 1, characterized in that In step (2), the mass ratio of Fe / ZIF-8 to Se powder is 5 to 20:
1.
8. The method according to claim 1, characterized in that In step (2), the carbonization is carried out in a tubular furnace. During the carbonization, the temperature is first raised to 700-1200° C. at a heating rate of 5° C. / min, and the temperature is maintained for 2-5 hours after the temperature is raised.
9. An Fe-Se / NC diatomic catalyst prepared according to the method according to any one of claims 1 to 8.
10. Use of the catalyst according to claim 9 in oxygen electroreduction and low-temperature rechargeable and dischargeable zinc-air batteries.
Citation Information
Patent Citations
Cu and Se diatomic catalyst as well as preparation method and application thereof
CN115332547A
Cited By
Preparation method of Co / Se diatomic site ORR catalyst supported by ZIF-derived porous carbon
CN117832521A
Carbon-metal composite material based on in-situ confinement hot pressing as well as preparation method and application of carbon-metal composite material
CN122177851A